« Who says that poetry makes nothing happen? » Paradoxes de l’engagement chez Ian McEwan - Elsa Cavalié (Études Britanniques Contemporaines, 2016)
This article looks at McEwan’s late fiction (2000-2014), and specifically focuses on the notion of engagement. Although it is obvious that McEwan considers himself engaged/involved in the contemporary world, the way his engagement/involvement is conveyed in his fiction is yet to be defined. McEwan’s fiction can first be described as belonging to the “Third Culture” (Brockman), an attempt at reconciling Science (in the broadest sense) and Art. Then it will be seen how, at the very heart of the novel, empathy is used in order to enable the reader to engage with narratives whose intricate constructions are thought to be a means to convey the novelist’s engagement in exploring the world. The paradox however lies in the fact that the unstable, postmodernist text such as Atonement and Sweet Tooth, rather than the neorealist novels such as Solar and Saturday succeed in having the reader fully engage with the text, on empathic, and ethical levels, for they provide a form of necessary instability.